Studi Komparasi Metode Pembelajaran dalam Meningkatkan Literasi Keuangan di Masa Pandemi Covid-19 - Satrio, Yogi Dwi; Handayani, Sri; Abbas, Muhammad Hasyim Ibnu; Kustiandi, Januar (Universitas Pendidikan Ganesha, 2020)
The COVID-19 pandemic attack the economy and society. Economic activity collapses, the economic activity of the community experiences a setback due to many socio-economic restrictions. The logic of economic action from consumption and production works out of reason. Financial literacy cannot be separated in life. Financial literacy is an important skill that can be used to make economic decisions. Many pre-pandemic programs have been carried out to increase Financial Literacy. In the field of education students have been taught to be more sensitive in applied economics, only an evaluation tool for the effectiveness of methods that have not been accommodated. Researchers examine the condition of financial literacy at university level students. Based on the learning methods applied during the pandemic, using the score collection method. The analytical method used in this study was an independent t-test based on the teaching method implemented, respondents were divided into 2 group, 46 students in online learning classes and 46 students in game based learning classes. The results showed that the learning method at home learning was not significant enough to develop individual financial literacy.